Diversitas Dewan Komisaris dan Pengaruhnya Terhadap Tingkat Pengungkapan Manajemen Risiko Perusahaan - Robby Ananda; Fajar Gustiawaty Dewi (Journal Economy and Currency Study (JECS), 2023)
One of the challenges facing the business world today is vulnerability to unwanted risks. For this reason, a comprehensive risk management system is needed to mitigate bad things and increase stakeholder confidence in the company. The leadership structure of Indonesian organizations that adheres to the two-tier concept by separating the roles and responsibilities of Commissioners and directors causes the board of Commissioners and directors to also carry out internal control functions. This leadership structure involves the commissioner's role in terms of risk management disclosure. On the other hand, the issue of diversity in public companies in Indonesia is a factor that affects the complexity of alternative decision-making that affects the disclosure of risk management. This study will examine the effect of diversity of Commissioners such as age, gender, and educational background on the level of disclosure of Corporate Risk Management. This study will take a sample of state-owned companies in Indonesia that are registered as members of the IDX during 2018-2019. This study will use the size of the company as a control variable. The analysis technique used is multiple regression analysis with a significance level of 5%. This study concluded that age diversity had no effect, while gender diversity and educational background diversity of company commissioners had an effect on risk management disclosure. This study shows that in addition to government regulations that have not been fully implemented on risk management disclosure obligations, it also shows that the background of the board of commissioners can affect the level of disclosure of the company's risk management in general. Transparency of risk management information will affect the level of confidence of investors and external stakeholders in the resilience and ability of the company in the face of uncertain situations.